Relationship between Quality Costs and Strategic Performance (Empirical Study on Industrial Companies in the Gaza Strip) - Amer, Reem; Dorgham, Maher (The Arab Journal of Administration, 2018)
The study aims to explore the relationship between quality costs (prevention costs, appraisal costs, internal failure costs, and external failure costs) and strategic performance (financial performance, operational performance, competitive performance) of the Palestinian industrial companies. To achieve the study goal, primary and secondary data were used and a questionnaire was designed to address the study topic and goals. (60) questionnaires were handed out to the management boards of industrial companies in the Gaza Strip, (53) questionnaires were hand-filled and returned with a return rate (88,3%). The study used the descriptive and statistical method to describe and analyze the study variables. The study results were as follows: the industrial companies apply quality costs (prevention, appraisal, internal failure and external failure costs) with a total percentage 79.13%, the results also indicated an increase in the strategic performance levels with a total percentage 83.46% as a result of introducing quality costs by these companies. Further it turned out that there was a statistically significant relationship between the application of quality costs and strategic performance of the industrial companies in the Gaza Strip. The study concluded with a number of recommendations, the most important of which were as follows; the management boards of industrial companies need to pay more attention to the quality costs and report them in the financial statements due to their significance in reducing the costs and increasing the revenues, such a matter will have a positive impact on the strategic performance of industrial companies; the industrial companies in the Gaza Strip need to pay more attention to the prevention and appraisal costs on one hand, since increasing these costs shall lead to reducing the internal and external failure costs; and encouraging the industrial companies to obtain quality certification and produce high-quality and defect-free products.